Response of Jute Mallow (Corchorus Olitorus) to Varying Levels of Cow Dung and NPK Application (Global Journal of Science Frontier Research, 2020)
The experiment was conducted in the raining seasons of 2016 and 2017 at the Kogi State University Teaching and Research farm to evaluate the effect of cow dung and mineral NPK (15:15:15) on the growth and yield performance of Corchorusolitorius The experiment, a 2*4 Factorial Experiment with four replications consisted of two nutrient sources (Organic and inorganic) as well as four levels of cow dung (0 ton/ha, 2 ton/ha, 4 ton/ha and 6 ton/ha) and four levels of mineral fertilizers NPK 15-15-15 (0 kg/ha, 50 kg/ha, 100 kg/ha, and150 kg/ha). The seeds were immersed in hot water at 97 oC for 10 seconds and then allowed to dry overnight before direct seeding on flat top ridges. Generally results obtained showed significant (P≤ 0.05) response of Corchorusolitorius to increasing rates of either cow dung or NPK 15:15:15 for plant height, leaf number, stem girth, number of branches, number of pods, pod weight per plant and total leaf harvest, compared to the control.
Keywords: growth; development; number of branches; number of pods; leaf harvest and yield